36‐1: Invited Paper: High‐Resolution Induced‐Electrohydrodynamic (iEHD) Jet Printing for Display. Issue 1 (25th September 2020) - Byun, Doyoung; Kang, Giho; Bin, Zhang; Jang, Yonghee; Jeon, Kwang Seon; Seong, Baekhoon; Son, Wonil; Nguyen, Vu Dat
Abstract : This talk includes an overview of high‐resolution electrohydrodynamic(EHD) jet printing method for display. With the EHD jet printing method, ones could overcome some limitations of conventional inkjet printing such as ink viscosity and pattern resolution. On the other hand, to eject drops by the EHD method, an electrode should supply charge to the ink so that there is possibility of electro‐chemical reaction on the electrode in a nozzle. Here, we present novel technology to prevent from the electro‐chemical reaction, which is named as induced‐EHD method. We present several research results for display applications such as fabrication of 1µm width electrode for thin film transistor(TFT), patterning quantum, and patterning pads for micro‐LED display.